Hemorrhagic Manifestations among Dengue Patients in Tertiary care Hospitals of Rawalpindi Medical University Pakistan - Shahid, Rizwana; Zeb, Shazia; Khan, Sadia; Umar, Muhammad; Yasmeen, Sumaira; Khan, Muhammad Mujeeb; Khurram, Muhammad (Infectious Diseases Journal of Pakistan, 2022)
Objective: To determine the frequency of various hemorrhagic manifestations among patients presenting with different dengue clinical syndrome in tertiary care hospitals affiliated with Rawalpindi Medical University. Methods: A cross-sectional descriptive hospital record-based research was carried out in three tertiary care hospitals (Holy Family Hospital (HFH), Benazir Bhutto Hospital (BBH) and District Head Quarters (DHQ) Hospital) affiliated with Rawalpindi Medical University. The data was collected during dengue epidemic from September-November 2019 pertinent to demographics, various bleeding manifestations, dengue clinical syndrome and hospital stay through consecutive sampling. The data was analyzed by means of SPSS version 25.0 and Microsoft Excel 2010. Gender based differences in various haemorrhagic manifestations was statistically verified by application of chi square test. P < 0.05 was taken as significant. Results: Of the total 1928 dengue cases with bleeding manifestations, 73.4% were males. About 1248(64.7%), 466(24.2%) and 214(11.1%) were admitted in HFH, BBH and DHQ Hospital Rawalpindi respectively. Amongst diverse haemorrhagic manifestations 33.8% had hematuria while 34.1% and 25.6% had gum bleeding and maculopapular rash respectively. Males presented with hematuria (P<0.001), gum bleeding (P < 0.001) and rash (P<0.005) comparatively more than those of females. Conclusion: Dengue virus infections are more prevalent among males residing in Rawalpindi and Islamabad. It is deadly but curable. Timely and appropriate management of cases can result in significant reduction of death toll. Key words: Dengue epidemic, Dengue fever, Dengue hemorrhagic fever, Dengue shock syndrome, Tertiary care hospitals.